2018
DOI: 10.3390/biomedicines6040110
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Immune Landscape of Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is a molecularly heterogeneous hematological malignancy with variable response to treatment. Recurring cytogenetic abnormalities and molecular lesions identify AML patient subgroups with different survival probabilities; however, 50–70% of AML cases harbor either normal or risk-indeterminate karyotypes. The discovery of better biomarkers of clinical success and failure is therefore necessary to inform tailored therapeutic decisions. Harnessing the immune system against cancer with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 116 publications
0
36
0
Order By: Relevance
“…Several recurrent pan-cancer immune profiles have been identified and could serve as biomarkers for predicting clinical responses to immunotherapy or for tailoring personalized treatment strategies (7,8). Briefly, tumors with inflamed type I and II interferon (IFN)-driven immune microenvironments (informally designated as "hot") are ICB responsive, while "cold" "immune-desert" tumors would rather benefit from adoptive cell transfer or tumor-peptide vaccination (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several recurrent pan-cancer immune profiles have been identified and could serve as biomarkers for predicting clinical responses to immunotherapy or for tailoring personalized treatment strategies (7,8). Briefly, tumors with inflamed type I and II interferon (IFN)-driven immune microenvironments (informally designated as "hot") are ICB responsive, while "cold" "immune-desert" tumors would rather benefit from adoptive cell transfer or tumor-peptide vaccination (9).…”
Section: Introductionmentioning
confidence: 99%
“…The development of immunotherapy in acute myeloid leukemia (AML) has been hindered so far not only by its remarkable genetic, antigenic, and clonal heterogeneity (10)(11)(12)(13) and the risk of significant off-target hematologic toxicity but also by the lack of biomarkers defining patient populations more likely to benefit from it (9). Recent research revealed that immune profiles are identifiable in human AML and hold prognostic and therapeutic relevance (9,14). The AML immune response shares numerous traits with solid cancers (15) and offers various opportunities for immunotherapy (9).…”
Section: Introductionmentioning
confidence: 99%
“…For example, CD8+ T cell dysfunction in AML was in part reversible upon PD‐1 blockade in vitro, and PD‐1 blockade could enhance CD33‐CD3 BiTE antibody construct‐mediated cytotoxicity in AML . Thus, it would be interesting to further characterize the complexity of AML‐related T cell immunity, which might support the design of immunotherapies for AML …”
Section: Introductionmentioning
confidence: 99%
“…14,15 Thus, it would be interesting to further characterize the complexity of AML-related T cell immunity, which might support the design of immunotherapies for AML. 16 Based on TCR composition, T cells are divided in 2 types: TCR + and TCR + T cells. + T cells comprise the majority of T cells (90-95%) in peripheral blood and recognize antigens presented by APC with MHC restriction.…”
Section: Introductionmentioning
confidence: 99%
“…The immunophenotyping by flow cytometry is currently one of the fundamental pillars for the diagnosis and classification of lymphoproliferative and myeloid diseases (Craig and Foon, 2009). Immunologic dysregulation can be one cause of these diseases (Davidson-Moncada et al, 2018). The aim of the present study is to apply immunophenotyping as a tool in the biological monitoring of the gas station workers, helping in the diagnosis of benzene poisoning and in the prevention of hematological diseases.…”
Section: Introductionmentioning
confidence: 99%